Effects of Walnut Protein Peptides on Promotion of White Adipose Tissue Browning and Prevention of Obesity - Yankun FU; Yuzheng CAI; Zhiqiang FENG; Siru CHEN; Tianlin WANG; Lianjun SONG; Tiange LI (Shipin gongye ke-ji)
Objective: The aim of this study was to investigate the effect of walnut protein peptides (WPP) on the promotion of white adipose tissue (WAT) browning to prevent obesity. Methods: The 3T3-L1 preadipocytes were treated with WPP (0.25 mg/mL, 1.00 mg/mL) during the differentiation. Lipid accumulation, mitochondrial quantity, and the protein expression of key factors involved in WAT browning were detected in 3T3-L1 preadipocytes after differentiation. Furthermore, male C57BL/6 mice fed with high-fat diet (HFD) were treated with WPP (400 mg/kg BW) for 8 weeks. Body weight, adipose tissue weight and blood lipid levels were monitored, and oral glucose tolerance test (OGTT) was performed. The morphological changes of inguinal WAT were observed, and the protein expression of key factors involved in WAT browning were detected. Results: WPP treatment decreased the size of lipid droplets, reduced lipid accumulation, and increased mitochondrial quantity in 3T3-L1 adipocytes. Western blot results showed that WPP significantly up-regulated the protein expression level of key factors involved in WAT browning uncoupling protein 1 (UCP1), peroxisomal proliferator-activated receptor γ coactivator-1α (PGC-1α), PR domain-containing 16 (PRDM16), and peroxisomal proliferator-activated receptor α (PPARα). Compared with the HFD group, WPP intervention for 8 weeks significantly alleviated the body weight gain and reduced the WAT (epididymal fat, inguinal fat) mass index. WPP reduced the serum levels of triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) in HFD mice, while increased high-density lipoprotein cholesterol (HDL-C) levels and glucose tolerance. The results of H&E staining and UCP1 immunohistochemistry of inguinal WAT showed that WPP significantly reduced the increase in the average adipocyte area caused by HFD, and increased the number of UCP1 positive cells. In addition, compared with HFD group, WPP also increased the protein expression levels of UCP1, PGC-1α, PRDM16 and PPARα in inguinal WAT. Conclusions: WPP can promote the browning of WAT and prevent obesity and metabolic disorders induced by HFD, which provides potential as a functional food ingredient for preventing obesity.